Influence of Constant and Monotonic Loadings on Subsequent Biaxial Behaviour of 15 HM Boiler Steel - Kowalewski, Z. L. (Engineering Transactions, 1996)
Experimental analysis is presented of the plastic properties of 15 HM boiler steel in the as-received state and of the same material subjected to various types of predeformation. The analysis was made by studying the positions in the stress space and typical dimensions of the yield surfaces. The initial yield surface has been determined using the technique of sequential probes of the single specimen and this surface was used as the starting point for comparative studies of yield surfaces of the prestrained material. The material predeformations were induced either by a creep process or by monotonic loading, both at ambient temperature. After predeformation, yield surfaces were determined by the same method as that for the non-prestrained material. The anisotropic yield condition was used to create a least squares fit of the experimental results. Prior cold work induced the weakening effect of the steel in the considered plastic strain range. The material tested after prestraining, independently of the predeformation type, exhibited the Bauschinger effect.